2016
DOI: 10.1111/sed.12289
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary characteristics of palaeolake deposits along the Indus River valley, Ladakh, Trans‐Himalaya: Implications for the depositional environment

Abstract: This study is an attempt to contribute to the data set of granulometric studies of sediments by measuring the sedimentary structure and texture, along with statistical parameters, of cold and arid lake systems. The palaeolake sequence along the River Indus on the western fringe of the Tibetan Plateau in Ladakh sector was selected in order to shed light on depositional environmental changes within the lake from post-last glacial maximum to 5 ka. The River Indus was blocked by Lamayuru dam burst during the degla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…In our research endeavors in the Ladakh and Spiti regions of NW India, primarily dedicated to the Quaternary geomorphology and fluvio-lacustrine deposits, we have carried out extensive field reconnaissance surveys supported with laboratory-based dataset, and discussed the landscape evolution and paleoclimate of the region in our publications (Phartiyal et al, 2005(Phartiyal et al, , 2009a(Phartiyal et al, ,b, 2005(Phartiyal et al, , 2013(Phartiyal et al, , 2015Phartiyal and Sharma, 2009;Srivastava et al, 2013;Nag et al, 2016) and still continuing with it. A cursory look of the geomorphological signatures present in the entire NW Himalayan region (Figures 1-3) indicates that the region has experienced glacial advance (glacial phase) and retreat (interglacial phase) at different time intervals.…”
Section: Discussionmentioning
confidence: 99%
“…In our research endeavors in the Ladakh and Spiti regions of NW India, primarily dedicated to the Quaternary geomorphology and fluvio-lacustrine deposits, we have carried out extensive field reconnaissance surveys supported with laboratory-based dataset, and discussed the landscape evolution and paleoclimate of the region in our publications (Phartiyal et al, 2005(Phartiyal et al, , 2009a(Phartiyal et al, ,b, 2005(Phartiyal et al, , 2013(Phartiyal et al, , 2015Phartiyal and Sharma, 2009;Srivastava et al, 2013;Nag et al, 2016) and still continuing with it. A cursory look of the geomorphological signatures present in the entire NW Himalayan region (Figures 1-3) indicates that the region has experienced glacial advance (glacial phase) and retreat (interglacial phase) at different time intervals.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the ~35 m Spituk lake sequence took >100 ka to aggrade; implying an average sedimentation rate of 0.35 mm/yr, which is not realistic. The varve and sedimentary rythmites in the Spituk sequence that are supposed to be annual sedimentary layers are less than a centimeter in thickness indicating a much higher sedimentation rate (3–4 mm/yr; Nag et al, 2016). The chronological data published from the paleolake sequences from across the Himalaya also seem to suggest much higher sedimentation rates (Fort, 2000; Korup et al, 2006; Phartiyal et al, 2009; Anoop et al, 2013; Srivastava et al, 2013; Nag and Phartiya, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The valley-fill sequences along the Tangste River (Trans-Himalaya) show two phases of aggradation at 48 and 30-21 ka (Phartiyal et al, 2015). Further, a study establishing the chronology of the paleolake deposits along the Indus River suggested three phases of lake formation during warm and wet climate at ~35-26 ka (Lamayuru palaeolake); 17-13 ka (Rizong palaeolake), and 14-5 ka (Khalsi-Saspol palaeolake) (Nag and Phartiyal, 2015;Nag et al, 2016). Episodic filling in the valley was caused by glaciogenic, fluvial, lacustrine, and alluvial sedimentation during intensified monsoon periods (Phartiyal et al, 2015).…”
Section: Sedimentation In the Northern Hinterlandmentioning
confidence: 99%